The Effect of Using Miming Game Combined With Jumble Words Game on Students’ Vocabulary Mastery (Quasi Experimental at The Fourth Grade of SD IT Al Qiswah Kota Bengkulu In The Academic Year 2021/2022) - Viomeika , Deanta; Akbarjono, Ali; Martina, Feny (JPT : Jurnal Pendidikan Tematik, 2022)
The objective of this research is to investigate the effect of using miming game combined with jumble words game on students’ vocabulary at the fourth grade of SD IT Al Qiswah Bengkulu city in the academic year 2021/2022. This research was conducted by used time series design, in which only used one class as a experiment class. This research conducted in three series, there are three meeting for pre-test, three meeting for treatment and 3 meeting for post-test. Vocabulary test was used to collect data. One sample t-test formula was used to testing hypothesis with requirement data is distribute normal. In this research used kolmogrov smirnov to test normality th data . The result of this research, the means score of post-test the experimental group class 88,18 was higher than the mean score of pre-test of the experimental group class 69,21. In other words Ha was accepted and Ho was rejected. It can be concluded that teaching by using miming game combined with jumble words game has significant effect on students’ vocabulary mastery at fourth grade of SD IT Al-Qiswah Kota Bengkulu in the academic year 2021/2022. This research has several significances for theoritical and partical contribution.